HAMBATAN-HAMBATAN GURU IPA SMP DI KOTA PEKANBARU DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 TAHUN AJARAN 2013/2014 - Sari, Wulan Sari; Natalina, Mariani Natalina; ', Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the barriers junior high science teacher in the city of Pekanbaru in the implementation of Curriculum 2013 school year 2013/2014. This study was conducted from October to December 2014. The sample as many as 10 teachers IPA junior class VII Public and Private Pekanbaru city which was subjected to the implementation of Curriculum 2013, which was selected by purposive sampling technique. Data collection instruments included in the form of an open questionnaire and observation. Open questionnaire statement amounted to 35 items divided into three indicators, namely the planning, implementation and evaluation. Teacher activity observation sheet with three indicators that preparatory activities, core activities, and closing activities. Data were analyzed by descriptive. Junior high science teacher barriers in the city of Pekanbaru in the implementation of Curriculum 2013 were less criteria barriers with an average (0.4), indicating the average score on each indicator, namely planning (0.5), implementation (0, 3), and evaluation (0.4). The average activity of teachers to the teaching and learning junior high science teacher in the city of Pekanbaru in the implementation of Curriculum 2013 for SMP on the preparatory activities (67.9), the core (89.1), and the cover activities ( 28.6). As for the private high school in the preparatory activities (66.7), the core (81), and cover activities (29.2). This suggests a science teacher in junior class VII Pekanbaru city in the implementation of Curriculum 2013, there were some barriers to understand the syllabus Curriculum 2013 Curriculum 2013 RPP preparation, preparation of authentic assessment techniques, apply a scientific approach (scientific) through the selected model, interaction during the learning and assessment of learning outcomes.Keywords: Barriers, Implementation of Curriculum 201, Learning science